The Human Desire To Struggle, An Analysis On The Truman Show - Susanto, Raka Meydha Putra; Varen, Nathaniel (English Journal Antartika, 2023)
Humans always dream of reaching the truth. No matter how hard it is, it is written in the human spirit. It is why humans keep moving forward despite how tough it is. The Truman Show is a social satire movie that explores themes of controlled truth, faith, and human struggle. The Truman Show's social commentary on how the media controls human life is depicted by the main character, Truman Burbank, a man who doesn’t realize that his life is being recorded all day and all night. This paper aims to analyze the nature of the human desire to know the truth. The researchers will look at the main character’s journey from the beginning until the end of the story. This research used the Qualitative Method and the Existentialism philosophy as its basis.